Palatal hyperplasia associated with hereditary gingival fibromatosis. (2nd February 2022) - Patrick, Amy; Savla, Adesh; Eyeson, Josiah
Abstract : Hereditary gingival fibromatosis (HGF) is a benign, non-haemorrhagic, fibrous gingival overgrowth of unknown cause. Clinically, gingivae can be seen to partially or fully cover teeth, and can limit oral function, for example eating, speaking, and maintaining oral hygiene. HGF normally starts in the transition between the primary and secondary dentition. Surgical excision is often required. This case describes the management of a 37-year-old male with generalized HGF with extensive bilateral palatal growths extending into the oropharynx; not a reported presentation of HGF. Awareness of the condition and familial history could aid management at an earlier stage. CPD/Clinical Relevance: This article describes the management of an uncommon presentation of hereditary gingival fibromatosis in the palate that affected the patient's oral function.